PTPN14 Forms a Complex with Kibra and LATS1 Proteins and Negatively Regulates the YAP Oncogenic Function - Wilson, Kayla E. (American Society for Biochemistry and Molecular Biology, 2014)
The Hippo signaling pathway regulates cellular proliferation and survival, thus exerting profound effects on normal cell fate and tumorigenesis. Pivotal effectors of this pathway are YAP/TAZ, transcriptional co-activators whose dysfunction contributes to epithelial-to-mesenchymal transition and malignant transformation. Therefore, it is of great importance to decipher the mechanisms underlying the regulations of YAP/TAZ at various levels. Here we report that non-receptor tyrosine phosphatase 14 (PTPN14) interacts with the Kibra protein. The interaction between PTPN14 and Kibra is through the PPXY domain of PTPN14 and WW domain of Kibra. PTPN14 and Kibra can induce the LATS1 activation independently and cooperatively. Interestingly, activation of LATS1 by PTPN14 is dependent on the C terminus of PTPN14 and independent of the upstream mammalian STE20-like kinase (MST) proteins. Furthermore, we demonstrate that PTPN14 increases the LAST1 protein stability. Last, overexpression of Kibra rescues the increased cell migration and aberrant three-dimensional morphogenesis induced by knockdown of PTPN14, and this rescue is mediated through the activation of the upstream LATS1 kinase and subsequent cytoplasmic sequestration of YAP. In summary, our results indicate a potential regulatory role of PTPN14 in the Hippo pathway and demonstrate another layer of regulation in the YAP oncogenic function.